Racial Differences of Pediatric Hypertension in Relation to Birth Weight and Body Size in the United States. - Liwei Chen; Neal Simonsen; Li Liu (PLoS ONE, 2015)
The prevalence of hypertension is known to differ by racial group in adults in the United States (US), but findings in children are scarce and inconsistent. The objective of this study was to assess the racial differences in pediatric hypertension and to explore whether these differences, if any, can be explained by low birth weight (LBW) and obesity.Analyses were performed for participants aged 8-17 years (N = 9,250) included in the 1999-2010 National Health and Nutrition Examination Survey. Multivariate logistic regressions and weighted analysis were carried out considering the complex survey design.Compared to non-Hispanic White youth, the crude prevalence of hypertension was significantly higher in non-Hispanic Blacks (7.1% vs. 5.6%; P = 0.04), but not in Mexican Americans (5.4% vs. 5.6%; P = 0.77). Blacks also had higher rates of LBW (14.6% vs. 5.9%; P <0.001) and obesity (22.9% vs. 15.8%; P <0.001) than Whites. In stratified analysis by age-sex groups, the Black-White difference in hypertension prevalence was only significant in boys aged 13-17 (9.6% vs. 6.6%). After controlling for age, Black boys had a 51% higher odds of having hypertension (Odds ratio = 1.51; 95% confidence interval: 1.03, 3.43; P = 0.04) compared to White youth at ages 13-17. This racial difference persisted with additional adjustment for birth weight (odds ratio (OR) = 2.00; P = 0.02) and for current body mass index (OR = 1.50; P = 0.04). Mexican American youth had no difference in hypertension prevalence as compared to White youth after adjusting for age, sex, birth weight and obesity (Odds ratio = 0.82; P = 0.16) and in age-sex stratified subgroups.Non-Hispanic Black adolescent boys have a significantly higher hypertension rate than their non-Hispanic White counterparts in the US. This racial difference cannot be explained by LBW and current obesity status within the Black population.